1998
DOI: 10.1046/j.1471-4159.1998.70031104.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Activation of Metabotropic Glutamate Receptors Inhibits the Handling‐Induced Increased Release of Dopamine in the Nucleus Accumbens but Not that of Dopamine or Noradrenaline in the Prefrontal Cortex: Comparison with Inhibition of Ionotropic Receptors

Abstract: On-line in vivo microdialysis was used to determine the effects of a 16-mm handling period on release of dopamine (DA) in the nucleus accumbens and of DA and noradrenaline (NA) in the medial prefrontal cortex of awake, freely moving rats. DA and NA were determined in one HPLC run. Handling resulted in an immediate and strong increase of both catecholamines in the prefrontal cortex. Maximal values for DA were 295%, and for NA 225%, of controls. DA in the nucleus accumbens was also increased (to 135% of controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 54 publications
(80 reference statements)
7
36
1
Order By: Relevance
“…2a), extracellular DA increased in response to ICV injection of PBS. As rats were not habituated to handling before the experiment, this likely reflects the effect of handling/injection stress (Feenstra et al 1998;Peleg-Raibstein et al 2005). mGlu1 and mGlu5 receptor mRNA and immunoreactivity are widely distributed in the brain including the mPFC and midbrain (Shigemoto et al 1992;Romano et al 1995;Petralia et al 1997;Lavreysen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2a), extracellular DA increased in response to ICV injection of PBS. As rats were not habituated to handling before the experiment, this likely reflects the effect of handling/injection stress (Feenstra et al 1998;Peleg-Raibstein et al 2005). mGlu1 and mGlu5 receptor mRNA and immunoreactivity are widely distributed in the brain including the mPFC and midbrain (Shigemoto et al 1992;Romano et al 1995;Petralia et al 1997;Lavreysen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, a non-NMDA glutamate receptor antagonist (DNQX) did not alter stressinduced changes in the mPFC NE overflow, whereas infusion of an NMDA glutamate receptor antagonist (CPP) reduced the stress-induced response of mPFC NE. Additionally, direct infusion of the GABA B agonist baclofen or glutamate receptor agonist and antagonists (ACPD, dixocilpine) into the mPFC did not alter stress-induced NE increases in this same region (Feenstra et al 1998). …”
Section: Noradrenergic Response To Mp Challenge and Stressmentioning
confidence: 91%
“…Additionally, findings by Doherty and Gratton (1999) indicate that infusion of a GABA A agonist (muscimol) directly into the PFC inhibits stress-induced release of DA in the mPFC, while a GABA B antagonist (phaclofen) enhances this same release. On the contrary, under similar conditions Feenstra et al (Feenstra et al 1998) found no influence of the locally applied GABA B agonist baclofen or glutamate receptor agonists and antagonists (ACPD, dixocilpine) in the mPFC, although in an earlier study (Feenstra et al 1995) this group reported a benzodiazepine (diazepam) to inhibit the stress-induced release of DA in the mPFC. Taken together, these studies indicate that GABA B antagonism and GABA A agonism could play a possible role in the enhanced DAergic response to MP challenge in the mPFC induced by stress, although additional investigations would be required to support this hypothesis.…”
Section: Brief Stress Enhances the Da Response To Mp When Administerementioning
confidence: 91%
See 1 more Smart Citation
“…Sham stimulation was applied as described above with the control rats receiving six trains of sham stimulation. As handling is known to be able to influence intracerebral DA release (Feenstra et al, 1998), control rats were treated in exactly the same way as the rTMS animals during all parts of the experiment.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%